PENERAPAN PEMBELAJARAN TEMATIK - Adinda Aryani; Al Qoriyani; Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2021)
Thematic learning models use themes from various subjects to provide meaningful learning experiences to students. In social studies learning in elementary schools, this model is applied by taking a theme and dividing it into several concepts that depend on students' basic competencies, which may be integrated at the same grade level. In addition, this model is combined with various student learning activities to make learning more interesting.Thematic learning includes several basic competencies, learning outcomes, and indicators from a subject, or even more than one subject. It is expected that students can learn and play with high creativity during thematic learning.Thematic learning is more focused on learning by doing (learning by doing). As a result, teachers must arrange or create learning experiences that affect the meaning of student learning. Learning experiences that show the relationship between conceptual elements make the learning process more effective. The conceptual link between the subjects studied will form a schema that allows students to gain completeness and completeness of knowledge.